The Role of Public Relations in Improving Image and Visibility of Tourism Destinations in Mandalika - Rendro Dhani (Ikatan Sarjana Komunikasi Indonesia, 2024)
Mandalika has recently been designated Indonesia’s Tourism Special Economic Zone (SEZ). The area is projected to become one of the ten New Bali. Establishing a tourism SEZ is one of the government’s agendas to accelerate the achievement of national economic development. Located on Lombok Island, Mandalika has attracted international attention after improving its infrastructure and hosting the prestigious MotoGP races. Lombok is well-known among Muslim tourists for its halal tourism, which has been ranked in the top several times. However, tourist visits to the destination have not been significant despite the local government’s efforts to improve its halal and sports tourism attractiveness. This study aims to investigate the role and practices of public relations in enhancing the image and visibility of Mandalika as a case study. This descriptive-qualitative study employs semi-structured interviews (n=16), field observations, sensory data, and online news and social media monitoring as data collection techniques. The study’s findings suggest that local governments and event organizers need help to maximize their communication strategies and more aggressively implement public relations practices crucial to enhancing the destination’s image and visibility for international and domestic tourists. As one of the underdeveloped regions in the country, technical support and regular financial assistance from the central government are also needed to make this destination self-sufficient and more attractive to visitors.